SMALL-SCALE VARIATIONS IN LEAF SHAPE UNDER ANTHROPOGENIC DISTURBANCE IN DIOECIOUS FOREST FORB MERCURIALIS PERENNIS: A GEOMETRIC MORPHOMETRIC EXAMINATION - Vujić, Vukica; Rubinjoni, Luka; Selaković, Sara; Cvetković, Dragana (Archives of Biological Sciences, 2016)
Plants are exposed to increasing levels of diverse human activities that have profound effects on their overall morphology and, specifically, on leaf morphology. Anthropogenic disturbances in urban and suburban forest recreational sites are attracting growing research interest. To explore the persisting recreational impact on leaf shape and size, we conducted a field study on the dioecious forb Mercurialis perennis L. (Euphorbiaceae), typical for undisturbed understory communities. We selected adjacent sites in a suburban forest, which experience contrasting regimes of disturbance by human trampling under otherwise concordant natural conditions. Patterns of leaf shape and size variation and putative sex-specific response to disturbance were analyzed using a geometric morphometric approach. In addition to leaf-level data, plant height, internode and leaf number were analyzed to explore the same response at the whole-plant level. The results show significant variations associated with disturbance at both levels: plants growing under a heavy disturbance regime had shorter stems with a greater number of wider and shorter leaves. Significant differences between sites were also found for leaf size, with larger leaves observed in an undisturbed site. The effects of sex and sex x site interaction on leaf size and shape were nonsignificant, pointing to the absence of sexual dimorphism and sex-specific response to disturbance. Contrary to leaf shape and size, all three analyzed shoot traits showed highly significant sexual dimorphism, with male plants being higher and having higher leaf and internode count. DOI: 10.2298/ABS151111011V Received: November 11, 2015; Revised: December 16, 2015; Accepted: December 16, 2015; Published online: January 21, 2016 How to cite this article: Vujić V, Rubinjoni L, Selaković S, Cvetković D. Small-scale variations in leaf shape under anthropogenic disturbance in dioecious forest forb mercurialis perennis: A geometric morphometric examination. Arch Biol Sci. 2016;68(4):705:13.